A retrospective study of the clinical characteristics of 9 children with pulmonary embolism associated with Mycoplasma pneumoniae pneumonia - Shaoxiu Song; Yongsheng Xu (BMC, 2023)
Abstract Objective The aim of this study was to analyze the clinical characteristics and treatment of children with Mycoplasma pneumoniae pneumonia (MPP) who also present with pulmonary embolism (PE). Methods This retrospective analysis examined the demographic data, clinical manifestations, laboratory tests, imaging characteristics, therapy, and prognosis of nine cases of children with Mycoplasma pneumoniae pneumonia (MPP) complicated by pulmonary embolism (PE). The study focused on patients admitted to the respiratory department of Tianjin Children's Hospital between January 2018 and December 2021. Results The age range of the patients was 3 to 8 years old, with a median age of 7.5 years. The median number of days from pulmonary infection to the diagnosis of embolism was 14 days. All patients had refractory Mycoplasma pneumoniae pneumonia (RMPP). Among them, three patients reported chest pain, one of whom had hemoptysis, while five patients had dyspnea, and six patients experienced radiating pain at unusual sites. Five out of the nine children tested positive for lupus anticoagulant (LA), five for anticardiolipin antibody (ACA), three for anti-2-glycoprotein antibody IgM, four for reduced protein S or protein C activity, and three for elevated coagulation factor VIII. Moreover, six out of the nine children tested positive for antinuclear antibodies. All the children underwent CT pulmonary angiograms, which revealed filling defects. After sequential low-molecular heparin anticoagulation with rivaroxaban, nine children in this study showed a good prognosis, with two of them receiving thrombolytic therapy for combined cardiac embolism. Follow-up at 0.5-9 months showed the gradual resolution of the emboli in all 9 children, with no thrombotic recurrences and normalized autoantibodies and thrombophilia markers. Conclusions The majority of cases involving Mycoplasma pneumoniae pneumonia (MPP) combined with pulmonary embolism (PE) were diagnosed with refractory MPP (RMPP). However, PE did not always occur in the advanced stages of the disease. Most patients presented with transient autoantibody positivity, abnormal coagulation, and fibrinolytic balance. With timely treatment, the prognosis of MPP combined with PE is generally good. Additionally, rivaroxaban treatment has been shown to be safe and effective.